Defining Severity of Hemophilia: More than Factor Levels - Pavlova, Anna; Oldenburg, Johannes (Seminars in Thrombosis and Hemostasis, 2013)
Patients with severe hemophilia generally exhibit a severe bleeding phenotype with bleeding into joints or muscles at an early age. Although the severity and frequency of bleeding symptoms correlate with the residual factor VIII/IX (FVIII/IX) activity in the plasma, a considerable variability in bleeding pattern, FVIII/IX concentrate utilization, and joint damage has been observed. A subset of 10 to 15% of patients with severe hemophilia A shows a milder disease phenotype with significantly reduced frequencies of spontaneous bleeding and lower requirements for factor concentrate. This mitigated clinical phenotype is determined by the underlying mutations in the F8/F9 genes, genetic alterations and polymorphisms in other genes of the hemostasis system, differences in inflammatory and immune response genes, limitations in laboratory diagnostics, as well as environmental factors. Identification of disease-modifying factors in hemophilia may influence treatment decisions, such as starting and tailoring prophylaxis according to the specific clinical phenotype, rather than just the laboratory-defined degree of severity. This review focuses on the current information of factors mitigating the clinical presentation of hemophilia and contributing to its high phenotypic heterogeneity.
Keywords: hemophilia; phenotype heterogeneity; factor FVIII/IX levels